The Miracle of Christ’s Resurrection in the Context of the Modern Science - Spasov, Chavdar (Forum Theologicum Sardicense, 2025)
Chavdar Spasov, The Miracle of Christ's Resurrection in the Context of the Modern Science. The main objective of this article is to contribute to the increasingly close interconnection of faith in God with various fields of science. In this instance, the focus is on physics, given its fundamental role as a natural science, specifically on the latest discoveries in quantum physics. Based on successfully conducted scientific experiments, quantum physicists today are able to provide scientific explanations for several so-called "inexplica-ble phenomena" or "miracles," among which many include Christ's Resurrection. It is suggested that not only quantum physics but also the modern "holographic idea of the universe" does not contradict theological knowledge and, therefore, faith in God.